Market-based incentives in developing countries: geographical dispersion, antecedents and implications of the Clean Development Mechanism. (23rd February 2017) - Fay, John; Kumar, Umesh
Abstract : The implementation of the Clean Development Mechanism (CDM) provides a flexible market-based incentive for addressing environmental risk in developing countries. While there has been a significant amount of ex-ante anecdotal and qualitative research regarding the CDM, there has been little ex-post, quantitative analysis of its antecedents based on a levelized comparison across developing countries. This article provides a quantitative analysis of CDM dispersion worldwide and investigates the relationship between the CDM and the overall host country governance, economic and social environment. Using multivariate regression analysis on a levelized basis, we find the Human Development Index to be a strong determinant of the CDM. This suggests the importance of non-economic factors and the need to tailor market-based instruments to the host country's level of social development. One-size-fits-all approach to reducing emissions in developing countries will not be effective to all countries.